Impact of Noninvasive Respiratory Support in Patients With COVID-19 Requiring V-V ECMO. Issue 2 (12th January 2022) - Ahmad, Qamar; Green, Adam; Chandel, Abhimanyu; Lantry, James; Desai, Mehul; Simou, Jikerkhoun; Osborn, Erik; Singh, Ramesh; Puri, Nitin; Moran, Patrick; Dalton, Heidi; Speir, Alan; et al.
Abstract : The impact of the duration of noninvasive respiratory support (RS) including high-flow nasal cannula and noninvasive ventilation before the initiation of extracorporeal membrane oxygenation (ECMO) is unknown. We reviewed data of patients with coronavirus disease 2019 (COVID-19) treated with V-V ECMO at two high-volume tertiary care centers. Survival analysis was used to compare the effect of duration of RS on liberation from ECMO. A total of 78 patients required ECMO and the median duration of RS and invasive mechanical ventilation (IMV) before ECMO was 2 days (interquartile range [IQR]: 0, 6) and 2.5 days (IQR: 1, 5), respectively. The median duration of ECMO support was 24 days (IQR: 11, 73) and 59.0% (N = 46) remained alive at the time of censure. Patients that received RS for ≥3 days were significantly less likely to be liberated from ECMO (HR: 0.46; 95% CI: 0.26–0.83), IMV (HR: 0.42; 95% CI: 0.20–0.89) or be discharged from the hospital (HR: 0.52; 95% CI: 0.27–0.99) compared to patients that received RS for <3 days. There was no difference in hospital mortality between the groups (HR: 1.12; 95% CI: 0.56–2.26). These relationships persisted after adjustment for age, gender, and duration of IMV. Prolonged duration of RS before ECMO may result in lung injury and worse subsequent outcomes.